How Green Marketing Orientation And Green Marketing Mix Helped Increasing Purchase Intention And Kept Customer Retention? - Steven Tanadi; Kurniawati Kurniawati (Journal Research of Social Science, Economics, and Management, 2025)
Purpose: With companies that began launching green products or services considered to be environmentally safe, companies began to contribute to making a safer environment. However, consumers lack the knowledge of what makes them skeptical of these green products. This research aims to see the influence of green marketing orientation and green marketing mix in influencing purchase intention and customer retention. Methodology: This research will be done by purposive sampling and uses cross-sectional form to gather respondents' data and acquired data will be then used to test each hypothesis regarding the influence of green marketing orientation and green marketing mix on purchase intention that would influence customer retention. Result: The result of the research proves that Green Marketing Mix and Green Marketing orientation does indeed influence purchase intention and would also influence customer retention afterward. By using SEM PLS 3 it was determined that all the hypotheses were proven to be accurate Implication: This research implied that Green Marketing Orientation and Green Marketing mix and marketing orientations influence purchase intentions as consumers have given information regarding what are the green elements in a green product. With one-time purchase intentions already made, customer retention would also be maintained or increased as purchase intentions helped to influence it.